2011
DOI: 10.1890/10-1176.1
|View full text |Cite
|
Sign up to set email alerts
|

Do mountain pine beetle outbreaks change the probability of active crown fire in lodgepole pine forests?

Abstract: Abstract. Disturbance interactions have received growing interest in ecological research in the last decade. Fire and bark beetle outbreaks have recently increased in severity and extent across western North America, raising concerns about their possible interactions. Although it is often presumed that bark beetle outbreaks increase probability of active crown fire by producing high loads of surface and canopy dead fuels, empirical data are scarce and results are ambivalent. We combined field measurements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
331
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 255 publications
(360 citation statements)
references
References 45 publications
22
331
7
Order By: Relevance
“…latifolia) (8). Severe MPB outbreaks can result in up to 90% mortality of tree basal area (14)(15)(16)(17)(18), which could compromise postfire resilience by increasing the severity of subsequent wildfires, decreasing seed sources (thus diminishing postfire tree regeneration), or both.…”
mentioning
confidence: 99%
“…latifolia) (8). Severe MPB outbreaks can result in up to 90% mortality of tree basal area (14)(15)(16)(17)(18), which could compromise postfire resilience by increasing the severity of subsequent wildfires, decreasing seed sources (thus diminishing postfire tree regeneration), or both.…”
mentioning
confidence: 99%
“…The authors of this article along with colleagues conducted a series of studies examining interactive impacts of P. ramorum and fire in coastal California forests. Using a set of permanent study plots in disease-impacted forests that were surveyed before and after the 2008 Basin Fire, this work showed that fire impacts are contingent on the stages of disease progression, supporting comparisons to insect-fire interactions (compare with [57]). In our plots, fire intensity was positively related to the amount of fine canopy fuels associated with recently killed trees and decreased as these materials move from the canopy to the soil surface [18].…”
Section: Disease-disturbance Interactionsmentioning
confidence: 60%
“…Severe insect-caused mortality often results in a short-term increase in highly flammable canopy fuels followed by an increase in ground fuels as dead material moves from the canopy to the forest floor. Somewhat counter to initial expectations, these mortality patterns have led to an overall decrease in fire impacts as measured by the likelihood of crown-fire, which are often the most damaging and dangerous forest fire conditions, for both bark beetle [11,57] and spruce budworm [58]. In these studies, the timing of fire and insect outbreak events was more important than the spatial overlap of each disturbance.…”
Section: Insect-fire Interactionsmentioning
confidence: 79%
See 2 more Smart Citations